Smartphone addiction and life satisfaction: mediating effect of negative emotions - Vallejos-Flores, Miguel Angel (2023)
Background: Smartphone users have increased worldwide, due to their multifunctionality and accessibility. Objective: To determine the mediating effect of negative emotions between life satisfaction and smartphone addiction in college students. Method: A structural equation explanatory model was proposed in which each negative emotion (depression, anxiety, and stress) has a mediating role between life satisfaction and cell phone addiction. To this end, 1109 university students from Metropolitan Lima were selected and administered the DASS 21, SABAS, SWLS. Result: A partial effect of each mediating model was found, in addition to Satisfaction with life achieved a direct effect on cell phone addiction; at the same time the mediating variables achieved a significant direct effect on addictive behavior. Conclusion: Negative emotions have a mediating role in explaining smartphone addiction.